1996
DOI: 10.1046/j.1365-313x.1996.10040713.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐linked oligosaccharide processing is not necessary for glycoprotein secretion in plants

Abstract: The role of N-glycans in the secretion of glycoproteins by suspension-cultured sycamore cells was studied. The transport of glycoproteins to the extracellular compartment was investigated in the presence of a glycan-processing inhibitor, castanospermine. Castanospermine has been selected because it inhibits homogeneously glycan maturation in sycamore cells and leads to the accumulation of a single immature N-glycan. The structure of this glycan has been identified as Glc3Man7GlcNAc2 by labeling experiments, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…c, chloroplast; cw, cell wall; f,¯agellum; G, Golgi stack; n, nucleus; sr, scale reticulum. Bars = 0.5 lm b Scale reticulum at 0 min and scale reticulum and multi-scale vesicles at 120 min might require N-glycosylation but not processing to complex glycans (Lerouge et al 1996). However, this might be not a general phenomenon because some glycoproteins are still secreted when N-glycosylation is inhibited (Capkova et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…c, chloroplast; cw, cell wall; f,¯agellum; G, Golgi stack; n, nucleus; sr, scale reticulum. Bars = 0.5 lm b Scale reticulum at 0 min and scale reticulum and multi-scale vesicles at 120 min might require N-glycosylation but not processing to complex glycans (Lerouge et al 1996). However, this might be not a general phenomenon because some glycoproteins are still secreted when N-glycosylation is inhibited (Capkova et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous tobacco and recombinant carrot cell wall invertases were immunoprecipitated from the microsomal (MI) and extracellular (MEX) protein extracts, analysed by SDS-PAGE and fluorography. obtained in different suspension-cultured plant cells clearly show that N-glycans are absolutely required for transport of glycoproteins to the cell surface (Hori and Elbein 1981, Faye and Chrispeels 1989, Driouich et al 1989) regardless of their oligosaccharide structure (Lerouge et al 1996).…”
Section: S]methionine and [mentioning
confidence: 94%
“…However, when N-glycosylation is prevented, an inhibition of glycoprotein transport to the cell surface is generally observed (Hori et al 1984, Ravi et al 1986, Driouich et al 1989, Faye and Chrispeels 1989 and a degradation of nonglycosylated extracellular glycoproteins takes place when the latter are transported without their N-glycans along the secretory pathway (Faye and Chrispeels 1989). Interestingly, the transport of plant glycoproteins to the cell surface is not affected if the maturation of their N-glycans is prevented by castanospermine (Lerouge et al 1996). Thus, the presence of N-glycans is necessary for an efficient transport of plant glycoproteins to the extracellular compartment independently of their oligosaccharide structure.…”
mentioning
confidence: 99%
“…Pulse chase experiments using ER glucosidase inhibitors in developing cotyledons or plant cell cultures have failed to show adverse in vivo effects on protein intracellular transport (Chrispeels and Vitale, 1985;Lerouge et al, 1996). Plant calnexin (Huang et al, 1993) and calreticulin (Denecke et al, 1995) have been cloned, and interactions have been shown between calnexin and the newly synthesized subunits of vacuolar H ϩ -ATPase (Li et al, 1998) and between calreticulin and BiP (Crofts et al, 1998).…”
Section: See You Next Yearmentioning
confidence: 99%
“…Indeed, several plant embryogenesis mutants are affected in other aspects of the secretory pathway, providing support for the notion that its full integrity is critical for plant life (reviewed in Sanderfoot et al, 2000;see Lukowitz et al, 2001). The in vivo pulse chase experiments performed previously may have been too limited in both the length of treatment with glucosidase inhibitors and the plant material used to allow the detection of detrimental effects (Chrispeels and Vitale, 1985;Lerouge et al, 1996). It will be interesting to determine if only a few key proteins are affected negatively by the absence of Glc removal or if this is a more general phenomenon.…”
Section: See You Next Yearmentioning
confidence: 99%